2013
DOI: 10.1007/s00264-013-2131-y
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical bilateral involvement of the hip in patients with slipped capital femoral epiphysis—a multicentre study

Abstract: These findings suggested the possibility of bilateral hip involvement in SCFE patients. Hips with greater degrees of PSA (> 19°) are likely to become symptomatic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…Several studies have demonstrated the significance of the posterior sloping angle (PSA) of the unaffected hip in predicting sequential SCFE. 8 , 10 , 12 , 21 , 22 Park et al 8 stated that PSA is predictive of sequential SCFE in patients presenting with unilateral SCFE. They recommend considering prophylactic screw fixation in females with PSA greater than13º upon presentation.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated the significance of the posterior sloping angle (PSA) of the unaffected hip in predicting sequential SCFE. 8 , 10 , 12 , 21 , 22 Park et al 8 stated that PSA is predictive of sequential SCFE in patients presenting with unilateral SCFE. They recommend considering prophylactic screw fixation in females with PSA greater than13º upon presentation.…”
Section: Resultsmentioning
confidence: 99%
“…Kohno et al found that ~70% of contralateral hips in unilateral SCFE patients had a subclinical posterior inclination of the capital femoral epiphysis, indicating the possibility of bilateral involvement. The contralateral posterior sloping angle was a reliable predictor of a contralateral slip, and an angle of 19° was the cutoff value for developing SCFE 12…”
Section: Etiology and Histopathologymentioning
confidence: 94%
“…Epiphyseal tilt in the anterior plane was found to be slightly higher in the contralateral asymptomatic hips, meaning that on average, the epiphysis is a little more posteriorly tilted in comparison to the matched group. Two studies showed a more posteriorly tilted epiphysis assessed by higher posterior sloping angle in the contralateral hip in patients with unilateral SCFE compared with control hips [3,17]. Increased posterior epiphyseal tilt (higher posterior sloping angle) is associated with an increased risk of sequential contralateral SCFE [4], and the posterior sloping angle has been used as a recommendation for prophylactic fixation, although conflicting threshold values have been reported [3,4,20,28,29,38].…”
Section: Volume 476 Numbermentioning
confidence: 99%
“…The posterior sloping angle, which measures orientation of the femoral head in relation to the neck-diaphysis axis, has been used as a predictor for the risk of sequential SCFE [3,4,20,28,29,38]. Although two studies showed higher posterior sloping angle in the contralateral hip of patients with unilateral SCFE in comparison to control normal hips [3,17], there are limited data regarding morphologic features of the contralateral hip assessed by contemporary measurements of femoroacetabular impingement (FAI) [7,10,36]. Elevated a angle suggesting FAI with cam-type morphologic features in the contralateral hips of patients with unilateral SCFE was reported in two long-term studies [10,36].…”
Section: Introductionmentioning
confidence: 99%